2012
DOI: 10.1111/j.1742-4658.2012.08753.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray structure of a protease‐resistant mutant form of human galectin‐8 with two carbohydrate recognition domains

Abstract: Galectin-8 is a tandem-repeat-type b-galactoside-specific animal lectin possessing N-terminal and C-terminal carbohydrate recognition domains (N-CRD and C-CRD, respectively), with a difference in carbohydratebinding specificity, involved in cell-matrix interaction, malignant transformation, and cell adhesion. N-CRD shows strong affinity for a2-3-sialylated oligosaccharides, a feature unique to galectin-8. C-CRD usually shows lower affinity for oligosaccharides but higher affinity for N-glycan-type branched oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 47 publications
4
39
1
1
Order By: Relevance
“…S4) because it has been reported that GAL8 forms a dimer in vitro through its N-CRD 23 . Furthermore, the proposed dimer models of GAL8 are all different from our observations 19,20 . Therefore, we assessed the oligomeric state of GAL8 in solution, which showed clear monomer formation (Supplementary Fig.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…S4) because it has been reported that GAL8 forms a dimer in vitro through its N-CRD 23 . Furthermore, the proposed dimer models of GAL8 are all different from our observations 19,20 . Therefore, we assessed the oligomeric state of GAL8 in solution, which showed clear monomer formation (Supplementary Fig.…”
Section: Resultscontrasting
confidence: 99%
“…SEC-MALS data of GAL8 and N-CRD of GAL8 in the presence of NAD showed the same result as those in the absence of NAD (Supplementary Figs S1b and S9), suggesting that NAD has no effect on dimerization and also that GAL8 exists as a monomer in solution. The indole ring of Trp86 forms van der Waals contacts with one of the pentose rings of NAD in a similar manner observed in other galectins 13,19,20 , and the tryptophan residue is strictly conserved among all galectins (Supplementary Fig. S6).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Tandem-repeat type galectins are sensitive to proteases due to the long linker. To carry out X-ray crystal structure determinations of tandem-repeat type galectins with two CRDs, the galectins with a short linker (19) and/ or the protease-resistant mutant forms with a modified linker peptide were used (20)(21)(22).…”
Section: A Introductionmentioning
confidence: 99%